Metacognitive Online Discussion for Online Teaching: A Conceptual and Impact on Students Engagement and Mastery During Coronavirus Outbreaks - Mohamad Ariffin Abu Bakar , Norulhuda Ismail (International Journal of Advanced Science and Technology, 2020)
The online teaching is proposed as a platform to continue learning sessions during outbreaks.It is essential to introduce online teaching activity model that strengthen student metacognitiveregulation skills in order to maintain active learning and to ensure students mastery of themathematics concepts at the optimum level. This concept paper exposes the development andimpact of a metacognitive regulation learning strategy model in the process of creating an onlineteaching activity. This discussion interacts with both the needs and elements of the onlinelearning concept. The implications provide guidance and suggestions for developing effectivemathematics teaching and learning sessions through online platforms, especially for those inneed of a social distancing crisis